Tools for Scaffolding the Development of L2 Speaking in English-medium Higher Education: Lessons from Poland and Australia - Pitura, Joanna; Chang, Heejin (Theory and Practice of Second Language Acquisition, 2023)
Participating in oral L2 communication may be challenging for English-medium higher education students. While literature suggests that scaffolding facilitates the development of L2 speaking, research has not addressed the notion of tools for scaffolding its development. The aim of this study is twofold: (1) to investigate how scaffolding can be embodied in tool design to support L2 speaking and (2) to obtain and analyse student perceptions of the tools. We draw on questionnaire data gathered in two iterations of a larger design-based research study conducted in two contexts: English Studies students in Poland (N = 26) and culturally and linguistically diverse L2 learners in Australia (N = 12). This study illustrates how features of scaffolding were applied to map instructor, peer- and technology-based tools in terms of learning activities, resources, technology and feedback. The results suggest that these tools may cater to the multiple levels of student understanding and skill with regard to the development of L2 speaking found in modern L2 classrooms.